Turkey and European energy (in)security: What role for Turkey in European energy security following the Russian invasion of Ukraine? - Kadri Tastan (Stiftung Wissenschaft und Politik (SWP), 2022)
The desire of the European Union (EU) to reduce its dependency on Russia for gas and diversify its sources of supply by turning to the resources of Central Asia, the Middle East, and the Eastern Mediterranean regions theoretically gives Turkey a major role in the EU's diversification and energy security policy. However, this strategic role for Turkey seems to be overestimated, given the limited share of energy that transits through Turkey to Europe. With the Russian invasion and Europe's search for alternative energy sources in extremis, the old discussion resurfaces: Could Turkey become a major transit country for energy supplies? Given the structural changes that have occurred in the energy markets, the objective of decarbonisation, and of course the political and infrastructural challenges, it seems that this old dream will not come true this time either.
Keywords: 320